GLOBALIZATION AND NATIONAL VALUES - Alisher Olimjonovich Xakimov (Web of Journals Publishing, 2025)
It seems that spirituality is a criterion that leads a person to spiritual purity, and strengthens and exalts his soul with the rays of faith – faith. The place of a person in society is determined not by his material assets, but by his high spiritual image. Spirituality serves as a bridge connecting ancestors to generations, the past to today, and the present to the future.
Keywords: Value, spirituality, culture, human, people, education, upbringing, heritage, reform, personnel training.